A double-edged sword: materiality classifications of sustainability topics - Göttsche, Max; Griffin, Paul A.; Habermann, Florian; Schiemann, Frank; Spandel, Theresa (Review of Accounting Studies, 2025)
The Sustainability Accounting Standards Board (SASB) has classified sustainability topics as material or not material for investors. We leverage the staggered release of the SASB classifications from 2013 to 2016 to examine whether and how they prompt changes in U.S. firms' sustainability performance. We measure sustainability performance using RepRisk scores, which reflect environmental, social, and governance (ESG) incidents. We find that RepRisk scores on sustainability topics classified as material decrease following the release of SASB classifications. Conversely, incident scores on nonmaterial sustainability topics increase. This suggests that firms improve their sustainability performance on topics the SASB deems relevant for investors while simultaneously performing worse on irrelevant topics. Firms adjust their internal sustainability policies to mirror these changes. The changes in sustainability performance occur primarily through two channels. We document that higher exposure to the classifications from shareholder pressure and sustainability-linked executive compensation prompts managers to prioritize sustainability topics classified as relevant for investors over irrelevant ones.